(untitled) (International Journal of Environmental Sciences, 2025)
This study focuses on the green synthesis of silver nanoparticles (AgNPs) using Lactobacillus delbrueckii isolated from yogurt, and the evaluation of their antioxidant, antibacterial, and anticancer properties. The bacterial strain was identified through Gram staining, biochemical tests, and confirmed by 16S rRNA sequencing. The cell-free supernatant of L. delbrueckii was mixed with silver nitrate, leading to the formation of AgNPs, as indicated by a visible colour change from pale yellow to dark brown. The synthesized nanoparticles were characterized using UV-Vis spectroscopy, which showed a peak at 415 nm, FTIR analysis revealed functional groups involved in nanoparticle stabilization, and FE-SEM confirmed that the particles were spherical with an average size of 21.47 nm. The AgNPs exhibited notable antioxidant activity in the DPPH assay (IC₅₀ ≈ 100.42 μg/ml) and showed antibacterial effects against common pathogens such as Staphylococcus aureus, Bacillus subtilis, Escherichia coli, and Pseudomonas aeruginosa. In addition, the AgNPs demonstrated significant anticancer activity against HCT-116 human colorectal carcinoma cells, with an IC₅₀ of 85.44 μg/ml. These results suggest that L. delbrueckii-mediated silver nanoparticles have promising potential for biomedical applications. However, further studies are needed to optimize the synthesis process and assess their long-term safety and therapeutic efficacy.